Antecedent infections in Guillain‐Barré syndrome: a single‐center, prospective study. Issue 12 (12th November 2019) - Hao, Yanlei; Wang, Weifang; Jacobs, Bart C.; Qiao, Baojun; Chen, Mengshi; Liu, Daiqiang; Feng, Xungang; Wang, Yuzhong
Abstract: Objective: To investigate the spectrum of antecedent infections in Chinese patients with Guillain‐Barré syndrome (GBS) and analyze the infections‐related clinical phenotypes locally. Methods: A prospective case‐control study of 150 patients diagnosed with GBS and age‐ and sex‐matched neurological and healthy controls was performed to investigate recent infections of 14 pathogens serologically and collect the clinical data during a follow‐up of 12 months. Results: In total, 53% of patients with GBS had a positive serology for recent infection, including Campylobacter jejuni (27%), influenza A (17%) and B (16%), hepatitis A virus (5%), dengue virus (3%), cytomegalovirus (3%), Epstein–Barr virus (3%), Mycoplasma pneumoniae (2%), herpes simplex virus (2%), varicella‐zoster virus (1%), and rubella virus (1%). Serology for infections of hepatitis E virus, Haemophilus influenzae, and Zika virus was negative. There was a higher frequency of C. jejuni, influenza A, influenza B, and hepatitis A virus infections in GBS patients than both the neurological and healthy controls. C. jejuni infection was more frequent in younger GBS patients and was associated with antibodies against GM1, GalNAc‐GD1a, and GM1:galactocerebroside complex. Influenza B infection was associated with a pure motor form of GBS. Interpretation: C. jejuni, influenza A, influenza B, and hepatitis A virus serve as the most common cause of antecedent infections in GBS locally. Influenza B‐related GBS may represent a pure motor phenotype. Differences in the infectious spectrum worldwide may contribute to the geographical clinical heterogeneity of GBS.